Crisis communication and marketing strategy during covid-19 pandemic in Karang Anyer village - Faustyna (Faculty of Communications Science, Dr. Soetomo University, 2023)
This research explored how crisis communication relates to marketing strategies during the Covid-19 pandemic. Understanding marketing strategies is crucial for businesses and institutions, especially in local communities, to manage their operations before, during, and after a crisis. The study found that many business actors faced difficulties with marketing strategies due to a lack of comprehension of crisis communication during the pandemic. The researchers used qualitative methods with purposive sampling to ensure study quality. The results, integrating the Situational Communication Crisis Theory, are relevant in communication science. They revealed a mismatch between managers' crisis communication activities and the capabilities of an ideal public relations officer in executing marketing strategies. The study recommends implementing training on crisis communication related to marketing strategies to enhance product promotion effectiveness during crises. This understanding will empower businesses and institutions to navigate uncertainties better and maintain resilience.